Nonaxisymmetric dynamic response of imperfectly bonded buried fluid-filled orthotropic cylindrical shells - Dwivedi J.P.; Singh V.P.; Upadhyay P.C. (My University, 2025)
This paper is concerned with the nonaxisymmetric dynamic response of an imperfectly bonded fluid-filled buried orthotropic cylindrical shell excited by a plane longitudinal wave. A thick shell model, including the effect of shear deformation and rotary inertia, has been taken. For the wave propagation in the fluid inside the pipe, linear acoustic equation has been used. The effects of fluid presence on the shell displacements have been studied for different soil conditions and at various angles of incidence of the longitudinal wave. The effects of bond imperfection on the shell response have been compared with the effects realized due to the presence of fluid inside the pipeline. Effects of changes in the fluid density are also discussed. It is found that magnitude of the response of fluid-filled pipeline can become even more than that of an empty pipeline (without fluid), and, hence, it cannot be assumed that a fluid-filled pipeline will always furnish safe and conservative response. © 1996 by ASME.